Pregnancy Care for Patients With Super Morbid Obesity - Olerich, Kelsey; Soper, David; Delaney, Shani; Sterrett, Mary (Frontiers in Pediatrics, 2022)
The patient with obesity represents unique challenges to the medical community and, in the setting of pregnancy, additional risks to both mother and fetus. This document will focus on the risks and considerations needed to care for the women with obesity and her fetus during the antepartum, intrapartum, and immediate postpartum stages of pregnancy. Specific attention will be given to pregnancy in the setting of class III and super morbid obesity.